2017
DOI: 10.18632/oncotarget.16506
|View full text |Cite
|
Sign up to set email alerts
|

The G-protein coupled receptor 56, expressed in colonic stem and cancer cells, binds progastrin to promote proliferation and carcinogenesis

Abstract: Overexpression of human progastrin increases colonic mucosal proliferation and colorectal cancer progression in mice. The G-protein coupled receptor 56 (GPR56) is known to regulate cell adhesion, migration, proliferation and stem cell biology, but its expression in the gut has not been studied. We hypothesized that the promotion of colorectal cancer by progastrin may be mediated in part through GPR56. Here, we found that GPR56 expresses in rare colonic crypt cells that lineage trace colonic glands consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 49 publications
1
42
0
1
Order By: Relevance
“…For example, the aGPCR GPR56/ADGRG1 is involved in cortex development, oligodendrocyte development, muscle cell development, innate immunity, and cancer progression (11)(12)(13)(14)(15)(16)(17). Recent studies have highlighted the role of GPR56 in promoting progression of acute myeloid leukemia (18) and progastrin-dependent colon cancer (19) and suggested that a GPR56 inhibitor would be clinically desirable.…”
mentioning
confidence: 99%
“…For example, the aGPCR GPR56/ADGRG1 is involved in cortex development, oligodendrocyte development, muscle cell development, innate immunity, and cancer progression (11)(12)(13)(14)(15)(16)(17). Recent studies have highlighted the role of GPR56 in promoting progression of acute myeloid leukemia (18) and progastrin-dependent colon cancer (19) and suggested that a GPR56 inhibitor would be clinically desirable.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that loss of GPR56 in CRC cells lead to decreased migration, invasion, and resistance to chemotherapy (12, 13,16); all of which may potentially be regulated through the Src-Fak pathway. In fact, therapeutic inhibitors of Src have been shown to suppress CRC cell growth and adhesion and sensitize cells to chemotherapy (49)(50)(51).…”
Section: Fak Signaling and Cell Adhesion (Figs 4c-f)mentioning
confidence: 99%
“…Analysis of clinical data revealed a significant correlation between high GPR56 levels and poor outcome in acute myeloid leukemia, ovarian cancer, and colorectal cancer (CRC) (10)(11)(12)(13)(14)(15). In CRC, GPR56 was shown to promote drug resistance and drive tumor growth (12,13,16). On the contrary, GPR56 has been shown to be downregulated in metastatic melanoma and inhibitory to melanoma growth and metastasis (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cross-linking enzyme transglutaminase 2 (TG2) in HEK293 cells (Xu et al, 2006), the anticoagulant heparin in A375 melanoma cells (Chiang et al, 2016) and the stomach prohormone progastrin in colorectal cancer cells (Jin et al, 2017). Whereas activation of GPR56 by collagen III or an antibody directed against its N-terminal has been shown to couple to RhoA through G12/13 (Iguchi et al, 2008;Luo et al, 2011Luo et al, , 2014, recruitment of downstream signalling has not been demonstrated so far for TG2, heparin or progastrin, suggesting that collagen III is the main endogenous agonist of GPR56.…”
Section: Adhesion Gpcr Activation and Signallingmentioning
confidence: 99%